JIP1 Deficiency Protects Retinal Ganglion Cells From Apoptosis in a Rotenone-Induced Injury Model - Liu, Wenyi; Li, Xue; Chen, Xi; Zhang, Jieqiong; Luo, Linlin; Hu, Qiumei; Zhou, Jiaxing; Yan, Jun; Lin, Sen; Ye, Jian (Frontiers in Cell and Developmental Biology, 2019)
Retinal ganglion cells (RGCs) undergo apoptosis after injury. c-Jun N-terminal kinase (JNK)-interacting protein 1 (JIP1) is a scaffold protein that is relevant to JNK activation and is a known key molecule that regulates neuronal apoptosis. However, the specific role of JIP1 in the apoptosis of RGCs is currently undefined. Here, we used JIP1 gene knockout (KO) mice to investigate the importance of JIP1-JNK signaling in the apoptosis of RGCs in a rotenone-induced injury model. In adult JIP1 KO mice, the number and electrophysiological function of RGCs were not different from those of wild-type (WT) mice. Ablation of JIP1 attenuated the activation of JNK and the cleavage of caspase-3 in the retina after rotenone injury and contributed to a lower number of TUNEL-positive RGCs, a greater percentage of surviving RGCs, and a significant reduction in the electrophysiological functional loss of RGCs when compared to those in WT controls. We also found that JIP1 was located in the neurites of primary RGCs, but accumulated in the soma in response to rotenone treatment. Meanwhile, the number of TUNEL-positive RGCs, the activation of JNK and the cleavage of caspase-3 were reduced in primary JIP1-deficient RGCs after rotenone injury compared to those in WT controls. Together, our results demonstrate that JIP1 deficiency-mediated activation of JNK contributes to the apoptosis of RGCs in a rotenone-induced injury model in vitro and in vivo, suggesting that JIP1 may be a potential therapeutic target for RGC degeneration.